Predictions of state and county top civil servants regarding the abolition of county state administration offices: two sides of the same coin? - Lopižić, Iva (Central European Public Administration Review, 2021)
In January 2020, county state administration offices, as first-line state administration offices in Croatia, were abolished and their competences transferred to county second-level units of local self-government. This organizational change represents administrative decentralization. The purpose of this article is to examine whether there are any differences in the predictions regarding the effects of this organizational change between two groups of civil servants: state civil servants (heads of county state administration offices and heads of their internal organizational units) and county civil servants (heads of county organizational units), and which are the factors that shape their predictions. A questionnaire was sent to the respondents in June 2019. The statistical analysis of the data (response rate 52%) shows a statistically significant difference between the predictions of the two groups in relation to all four categories of effects of this organizational change (inputs, processes, outputs, and outcomes). There is only one point where there is no difference: both groups agree that the county governor's role will grow. The difference in predictions is explained by two factors of cognitive biases: the organization's interest to survive and expand its power, and uncertainty (strategic, structural, and job-related). The paper offers an academic contribution to the field of administrative decentralization by giving insights into the predictions of different actors on the effects of such change before its implementation and by introducing factors of cognitive biases as explanations for discrepancies in the predictions.
Keywords: abolition of county state administration offices; administrative decentralization; civil servants' predictions; dejavniki kognitivne pristranskosti; factors of cognitive biases; predvidevanja javnih uslužbencev; ukinitev okrožnih uradov državne uprave; upravna decentralizacija